Concurrent changes in dental anxiety and smoking in parents of the FinnBrain Birth Cohort Study - Kallio Anu; Suominen Auli; Tolvanen Mimmi; Rantavuori Kari; Jussila Heidi; Karlsson Linnea; Karlsson Hasse; Lahti Satu (WILEY, 2025)
We evaluated associations between changes in dental anxiety and tobacco use, adjusted for general anxiety and depressive symptoms. The FinnBrain Birth Cohort Study data, collected at gestational weeks 14 and 34 and at 3 months postpartum, were used. Questionnaires included the Modified Dental Anxiety Scale (MDAS), the Edinburgh Postnatal Depression Scale (EPDS), and the anxiety subscale of the Symptom Checklist-90 (SCL). Smoking was categorized as "stable non-smoking", "started smoking", "quit smoking", and "stable smoking". Changes in smoking and dental anxiety were evaluated "during pregnancy" (i.e., from gestational week 14 to gestational week 34) in 2442 women and 1346 men and "after pregnancy" (i.e., from gestational week 34 to 3 months postpartum) in 2008 women and 1095 men. Changes were evaluated in three smoking categories (stable non-smoking, fluctuating, and stable smoking), using data from all three time-points (1979 women and 1049 men). Modeling used repeated measures analysis of covariance. Stable smoking mothers had statistically significantly higher levels of dental anxiety (mean MDAS 12.3-12.6) than non-smoking mothers (mean MDAS 10.1-10.7) or mothers who smoked at some point during pregnancy (mean MDAS 10.8-11.5). A similar tendency was observed in fathers. However, no systematic change in dental anxiety by changes in smoking habits was observed. Those smoking during pregnancy and with high dental anxiety may need special support for smoking cessation.